Robust Consensus Control for Multiple Euler–Lagrange Systems With External Disturbances Based on Event‐Triggered Communication - Shi, Zhengqing; Li, Bo; Zhou, Chuan; Guo, Jian (International journal of robust and nonlinear control, 2025)
ABSTRACT In this article, a novel robust consensus control protocol is proposed for multiple uncertain Euler–Lagrange systems with unknown external disturbances. First, the local adaptive control laws are derived under event‐triggered communication framework, and the robust consensus control problem is transformed into an equivalent optimal control problem with disturbance rejection. Event‐triggered mechanisms and distributed state estimators are designed by utilizing only triggered exchanging states, by which continuous monitoring neighbors' states is avoided and communication burdens are effectively reduced. Second, the Hamilton–Jacobi–Isaac equations are formulated based on zero‐sum differential game theory, and adaptive dynamic programming methods are employed to approximate the Nash‐equivalent solutions, by which the local robust optimal control laws are derived to eliminate the disturbance effects and improve the robustness of the proposed strategy. It is strictly proved that all signals in the closed‐loop systems are uniformly ultimately bounded and the cost functions are minimized. Finally, two practical examples are presented to validate the proposed strategy.